Feeding pigs and looking for güembé: The local production of knowledge about the natural world of peasant and indigenous children in San Ignacio - Padawer, Ana (2012)
Peasant and indigenous children habitually carry out productive activities in the forest and countryside as part of family reproduction. However, both scholars and common sense do not usually recognize these activities as implying knowledge. In this paper I will use the concepts of legitimate peripheral participation (Lave and Wenger 1991), communities of practice (Wenger 2001) and ethno-science (Ellen 2004) to identify situated learning outside school walls. These categories allow me to describe the knowledge of the natural and social world that peasant and Mbyà-Guaraní children from rural areas of San Ignacio (Misiones, Argentina) attain in their everyday learning experiences. Information about plants (their characteristics, properties and uses), and animals (food preferences, reproduction and environment) are learned by observing and doing, while science lessons usually tend to ignore such familiarity.